Study of the impact of cultivation conditions and peg surface modification on the in vitro biofilm formation of Staphylococcus aureus and Staphylococcus epidermidis in a system analogous to the Calgary biofilm device - Diepoltová, Adéla; Konečná, Klára; Janďourek, Ondřej; Nachtigal, Petr (Journal of medical microbiology, 2021)
Introduction. Staphylococcus aureus (SA) and Staphylococcus epidermidis (SE) are the most common pathogens from the genus Staphylococcus causing biofilm-associated infections. Generally, biofilm-associated infections represent a clinical challenge. Bacteria in biofilms are difficult to eradicate due to their resistance and serve as a reservoir for recurring persistent infections.Gap Statement. A variety of protocols for in vitro drug activity testing against staphylococcal biofilms have been introduced. However, there are often fundamental differences. All these differences in methodical approaches can then be reflected in the form of discrepancies between results.Aim. In this study, we aimed to develop optimal conditions for staphylococcal biofilm formation on pegs. The impact of peg surface modification was also studied.Methodology. The impact of tryptic soy broth alone or supplemented with foetal bovine serum (FBS) or human plasma (HP), together with the impact of the inoculum density of bacterial suspensions and the shaking versus the static mode of cultivation, on total biofilm biomass production in SA and SE reference strains was studied. The surface of pegs was modified with FBS, HP, or poly-l-lysine (PLL). The impact on total biofilm biomass was evaluated using the crystal violet staining method and statistical data analysis.Results. Tryptic soy broth supplemented with HP together with the shaking mode led to crucial potentiation of biofilm formation on pegs in SA strains. The SE strain did not produce biofilm biomass under the same conditions on pegs. Preconditioning of peg surfaces with FBS and HP led to a statistically significant increase in biofilm biomass formation in the SE strain.Conclusion. Optimal cultivation conditions for robust staphylococcal biofilm formation in vitro might differ among different bacterial strains and methodical approaches. The shaking mode and supplementation of cultivation medium with HP was beneficial for biofilm formation on pegs for SA (ATCC 29213) and methicillin-resistant SA (ATCC 43300). Peg conditioning with HP and PLL had no impact on biofilm formation in either of these strains. Peg coating with FBS showed an adverse effect on the biofilm formation of these strains. By contrast, there was a statistically significant increase in biofilm biomass production on pegs coated with FBS and HP for SE (ATCC 35983).
Keywords: matrix extracelulárních polymerních látek; Staphylococcus spp.; Extracellular Polymeric Substance Matrix; human plasma; biofilmy; Bacteriological Techniques; bakteriologické techniky; Animals; zvířata; Biofilms; Humans; peg surface modification; Species Specificity; kultivační média; biofilm formation; anti-biofilm activity screening; druhová specificita; Biomass; Calgary biofilm device; lidé; biomasa; Staphylococcus; Culture Media